2003
DOI: 10.1530/rep.0.1250425
|View full text |Cite
|
Sign up to set email alerts
|

Role of the angiotensin II system in regulation of ovulation and blood flow in the rat ovary

Abstract: The aim of the present study was to examine the roles of the angiotensin II receptor subtypes, AT 1 and AT 2 , in ovulation, and to evaluate the contribution of angiotensin II-mediated pathways in regulation of ovarian blood flow. The AT 1 -specific antagonist, losartan, was administered alone or in combination with the AT 2 -specific antagonist, PD123319, to preovulatory rat ovaries perfused in vitro. Losartan (100 mol l − 1 ) did not affect the number of ovulations, whereas the combination of losartan (100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…However, a selective nonpeptide antagonist for AGTR2 receptors (PD123,319) had no effects on the ovulation rate in in vitro-perfused rat ovaries (Mikuni et al 1998). Furthermore, the administration of PD123,319 diminished but did not completely block ovulation in rats (Mitsube et al 2003). Taken together, these results indicate that Ang II is essential for ovulation in rats, but this effect is not exclusively regulated via the AGTR2.…”
Section: Ang II Signaling and Receptors Near Ovulationmentioning
confidence: 86%
“…However, a selective nonpeptide antagonist for AGTR2 receptors (PD123,319) had no effects on the ovulation rate in in vitro-perfused rat ovaries (Mikuni et al 1998). Furthermore, the administration of PD123,319 diminished but did not completely block ovulation in rats (Mitsube et al 2003). Taken together, these results indicate that Ang II is essential for ovulation in rats, but this effect is not exclusively regulated via the AGTR2.…”
Section: Ang II Signaling and Receptors Near Ovulationmentioning
confidence: 86%
“…As mentioned above, the preovulatory increase in intrafollicular AngII may facilitate oocyte maturation (42) and ovulation (9,44) or the production of progesterone by human GL cells (45). Angiotensin II is increased in both follicular atresia (36,37) and corpus luteum regression (46), events that are known to be linked to apoptosis (47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that AT 1 receptormediated medullary vasodilator response to low doses of ANG II is mainly due to the release of PGs, whereas the dilator response to high doses has additional NO-and kinin-dependent components. Losartan had no effect on basal ovarian blood flow in rats but blocked the ANG II-induced flow reduction, and, in contrast, the AT 2 receptor antagonist PD123319 increased ovarian basal blood flow and failed to reverse the effect of exogenous ANG II, indicating that under physiological conditions, ovarian blood flow of the rat is negatively regulated by ANG II through AT 2 receptors (Mitsube et al, 2003). Bayraktutan and Ulker (2003) suggested that ANG II stimulates NO production in rat coronary microvascular endothelial cells in both an AT 1 -and AT 2 -receptorregulated manner.…”
Section: Involvement Of Angiotensin II Receptors Other Than Angiotensmentioning
confidence: 90%